Procurement of Essential Water Treatment Chemicals at the Ghana Water Company Limited - Jaylee, Synyenlentu (2015)
A Thesis Submitted to the Department Of Building Technology, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the award of Master of Science In Procurement Management, 2014